Blood Flow Restriction During Futsal Training Increases Muscle Activation and Strength - Amani-Shalamzari, Sadegh; Farhani, Farid; Rajabi, Hamid; Abbasi, Ali; Sarikhani, Ali; Paton, Carl; Bayati, Mahdi; Berdejo-del-Fresno, Daniel; Rosemann, Thomas; Nikolaidis, Pantelis Theodoros; Knechtle, Beat (Frontiers in Physiology, 2019)
The aim of this study was to investigate the effect of leg blood flow restriction (BFR) applied during a 3-a-side futsal game on strength-related parameters. Twelve male futsal players were randomly assigned into two groups (n=6 for each group) during 10 training sessions either with or without leg BFR. Prior to and post training sessions, participants completed a series of tests to assess anabolic hormones and leg strength. Pneumatic cuffs were initially inflated to 110% of systolic blood pressure and further increased by 10% after every two completed sessions. In comparison with baseline, the resting post-training levels of myostatin (p=0.002) and IGF-1/MSTN ratio (p=0.006) in the BFR group changed, whereas no change in the acute level of IGF-1 and myostatin after exercise was observed. Peak torque of knee extension and flexion increased in both groups (p<0.05). A trend of increased neural activation of all heads of the quadriceps was observed in both groups; however, it was statistically significant only for rectus femoris in BFR (p=0.02). These findings indicated that the addition of BFR to normal futsal training might induce greater neuromuscular benefits by increasing muscle activation and augmenting the hormonal response.